Immunogenicity and safety of an E. coli-produced bivalent human papillomavirus (type 16 and 18) vaccine: A randomized controlled phase 2 clinical trial. Issue 32 (31st July 2015) - Wu, Ting; Hu, Yue-Mei; Li, Juan; Chu, Kai; Huang, Shou-Jie; Zhao, Hui; Wang, Zhong-Ze; Yang, Chang-Lin; Jiang, Han-Min; Wang, Yi-Jun; Lin, Zhi-Jie; Pan, Hui-Rong; et al.
Highlights A dose-ranging study of a novel E. coli-expressed HPV 16/18 vaccine candidate. This is the first study of the immunogenicity of this recombinant HPV 16/18 vaccine. This vaccine was well-tolerated and appeared immunogenic in young women aged 18–25.